Code-to-Code Benchmark for Simulation Tools Based on the Unsteady Vortex-Lattice Method - Verstraete, Marcos Leonardo (2023)
Reliable aerodynamic and aeroelastic simulations of advanced aeronautical/mechanical systems require us to predict flow-induced forces as accurately as possible. Nowadays, computational fluid dynamic techniques are quite popular, but at an overwhelming computational cost. Consequently, methods like the unsteady vortex-lattice method (UVLM) became the workhorses for many simulation environments. Then, numerous UVLM-based codes using diverse numerical schemes, enhanced by several add-ons and implemented following different programming paradigms, were available in the literature. However, there is no set of benchmark cases intended for the systematic verification of those codes relying on the UVLM. Therefore, we provide six fully reproducible benchmark cases that can be used for such an end. We also describe two in-house UVLM-based codes that are well suited for aerodynamic simulations and for being encapsulated as an aerodynamic engine within partitioned aeroelastic simulation schemes. Because both codes follow radically different implementation philosophies, these represent excellent candidates to undergo the series of benchmark cases proposed. The work is completed by providing a valuable dataset and comparison criteria to measure to what extent two or more codes are in agreement. Along this path, for very first time, we use a comparison strategy to contrast free-wake methods based on the Hausdorff distance.